i think its the 2nd or 1st one
rlly tried here!
The equation of a circle centred at point (m,n) and radius r is given by
<span>(x-m)² + (y-n)² = r²
</span>-------------------------------------------------------------
Centre = (4,3)
radius = 5
Equation:
(x - 4)² + (y - 3)² = 5²
⇒ x² - 8x + 16 + y² - 6y + 9 = 25
⇒ x² + y² - 8x - 6y + 25 = 25
⇒ x² + y² - 8x - 6y = 0
The equation of the circle is x² + y² - 8x - 6y = 0
Hope it helps!
Answer:
see explanation
Step-by-step explanation:
Given
, ![\frac{7a}{a^2+11a+28}](https://tex.z-dn.net/?f=%5Cfrac%7B7a%7D%7Ba%5E2%2B11a%2B28%7D)
Factor the denominators of both fractions
, ![\frac{7a}{(a+4)(a+7)}](https://tex.z-dn.net/?f=%5Cfrac%7B7a%7D%7B%28a%2B4%29%28a%2B7%29%7D)
The lowest common denominator of both fractions is (a + 4)(a + 5)(a + 7)
Multiply numerator/denominator of first fraction by (a + 7)
Multiply numerator/denominator of second fraction by (a + 5 )
,
, then
, ![\frac{7a^2+35a}{(a+4)(a+5)(a+7)}](https://tex.z-dn.net/?f=%5Cfrac%7B7a%5E2%2B35a%7D%7B%28a%2B4%29%28a%2B5%29%28a%2B7%29%7D)